MANFAAT EKONOMI TAMAN NASIONAL GUNUNG CIREMAI BAGI MASYARAKAT DESA CISANTANA, KABUPATEN KUNINGAN - Maulida, Rahma Lia; Soekmadi, Rinekso; Hakim, Lukmanul (Universitas Nusa Bangsa, 2025)
Ciremai Mountain National Park is a conservation area that has significant ecological and social value for the surrounding community. However, the types and amounts of benefits obtained by the community from the utilization of these forest resources are not yet known. This study aims to estimate the economic value and analyze the utilization of Ciremai Mountain National Park for optimal management. The methods used include interviews, observations, and literature studies. The results show that the economic value of natural resources from grass, firewood, nature tourism, and water utilization has a total economic value of IDR 5,575,068,353 per year in 2024. The majority of the community does not fully understand the existence and benefits of Ciremai Mountain National Park, but its existence is still considered important. This is because the national park provides natural resources whose benefits are directly felt by the community. It is recommended that the utilization of grass and firewood be carried out sustainably and that the management of natural resources and water utilization permits be based on carrying capacity with the socialization of forest conservation around water sources.